Compliance with endogenous audit probabilities - Kai A. Konrad; Tim Lohse; Salmai Qari (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper studies the effect of endogenous audit probabilities on reporting behavior in a face-to-face compliance situation such as at customs. In an experimental setting in which underreporting has a higher expected payoff than truthful reporting we find an increase in compliance of about 80% if subjects have reason to believe that their behavior towards an officer influences their endogenous audit probability. Higher compliance is driven by considerations about how own appearance and performance affect their audit probability, rather than by social and psychological effects of face-to-face contact.
Keywords: H26; H31; C91; K42; 330; compliance; audit probability; tax evasion; face value; customs